Zbigniewa Herberta podróże do przeszłości = Zbigniew Herbert`s travels in the past - Konończuk, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Herbert`s essays collected in "Barbarzyńca w ogrodzie", "Martwa natura z wędzidłem" and "Labiryntnad morzem" are interpreted as an effort to know and understand the past as foreign country visitedby the writer. Using his imagination Herbert-traveller constructs images of the past.
Keywords: Herbert, Zbigniew (1924-1998) - twórczość; poezja polska - 20 w.; literatura polska - 20 w. - tematyka